Test process optimisation through big data analysis - Kho, Xiang Juan (2023)
The goal of the research is to adopt artificial intelligence techniques for regression test case selection in an industrial setting. Currently, the selection of test cases is made manually by test engineers referring to software change documentation. A machine learning-based solution which selects test cases with high potential in uncovering software defects is proposed and results were analysed.